Digestive Neuroendocrine Neoplasms (NEN): French Intergroup clinical practice guidelines for diagnosis, treatment and follow-up (SNFGE, GTE, RENATEN, TENPATH, FFCD, GERCOR, UNICANCER, SFCD, SFED, SFRO, SFR). Issue 5 (May 2020) - de Mestier, Louis; Lepage, Come; Baudin, Eric; Coriat, Romain; Courbon, Frédéric; Couvelard, Anne; Do Cao, Christine; Frampas, Eric; Gaujoux, Sébastien; Gincul, Rodica; Goudet, Pierre; Lombard-Bohas, Catherine; et al.
Abstract: Introduction: This document is a summary of the French Intergroup guidelines regarding the management of digestive neuroendocrine neoplasms (NEN) published in February 2020 (www.tncd.org ). Methods: All French medical societies involved in the management of NEN took part in this work. Recommendations were graded into four categories (A, B, C or D), according to the level of evidence found in the literature until May 2019. Results: The management of NEN is challenging because of their heterogeneity and the increasing complexity of diagnostic and therapeutic procedures. Pathological analysis is required for their diagnostic and prognostic characterization, which mainly relies on differentiation, grade and stage. The two main emergency situations are functioning syndromes and poorly-differentiated carcinoma. Chromogranin A is the main biochemical marker of NET, although of limited clinical interest. Initial characterization relies on morphological and isotopic imaging. The treatment of localized NET relies on watchful follow-up and local or surgical resection depending on its supposed aggressiveness. Treatment options for metastatic disease include surgery, somatostatin analogues, chemotherapy, targeted therapies, organ-driven locoregional therapies and peptide-receptor radionuclide therapy. As specific predictive factors of treatment efficacy are yet to be identified and head-to-head comparisons have not or only rarely been performed, the therapeutic strategy currently depends on prognostic factors. Cumulative toxicity and the impact of treatment on quality of life must be considered since survival is relatively long in most patients with NET. Conclusion: These guidelines are proposed to achieve the most beneficial therapeutic strategy in clinical practice as the therapeutic landscape of NEN is becoming ever more complex. These recommendations are permanently being reviewed.